A Comparative Study of Laser and MRI Efficiency in Stimulating Therapeutic Nanoparticles within Tumors - AbDulla, Maryam Rasol Arheem; Abood, Maryam Emad Slman; Ali, Zainab Hadi Abd; Zaji, Zahraa Hassan; Thaeab, Rusul Emad Yaser (American Journal of Botany and Bioengineering, 2025)
This study presents a comparative evaluation of laser and magnetic resonance imaging (MRI) modalities for stimulating therapeutic nanoparticles within tumor environments, addressing a critical knowledge gap in optimizing noninvasive cancer treatments. Using a mixed-methods approach involving clinical subjects with intracranial, prostate, and breast cancers, the efficiency of each modality was assessed through experimental stimulation and statistical analysis. Findings revealed that while both methods offer distinct benefits, MRI demonstrated superior stimulation efficiency and safety under constrained power conditions, especially in preserving vascular integrity. These results highlight MRI's potential as a preferred method for activating nanoparticles in targeted therapies, paving the way for safer and more effective oncological applications.